Training Undergraduate Students to Use Insight Skills: Integrating the Results of Three Studies. (August 2014) - Hill, Clara E.; Spangler, Patricia T.; Jackson, John L.; Chui, Harold
We compare the results of a series of studies (Chui et al., Jackson et al., and Spangler et al.) investigating the effects of training undergraduate students in helping skills courses to use insight skills (immediacy, challenges, interpretation) after they had learned exploration skills. A comparison of students and instructors indicated similarity across the samples. Increases in self-efficacy for the target skill were found across all studies. In addition, all components (reading, lecture, video modeling, practice, and feedback) were found to be effective, but students found practice and lecture to be particularly effective in all three studies. Higher initial self-efficacy for the target skill and higher prior helping experiences were associated with higher final levels of self-efficacy; lower self-efficacy for the target skill and higher prior helping experiences were associated with greater gains in self-efficacy over the course of training in two studies. Limitations and implications across all three studies are discussed.